Blood Neutrophil Count and Neutrophil‐to‐Lymphocyte Ratio for Prediction of Disease Progression and Mortality in Two Independent Systemic Sclerosis Cohorts. Issue 3 (17th November 2022) - Wareing, Nancy; Mohan, Vishnu; Taherian, Rana; Volkmann, Elizabeth R.; Lyons, Marka A.; Wilhalme, Holly; Roth, Michael D.; Estrada‐y‐Martin, Rosa M.; Skaug, Brian; Mayes, Maureen D.; Tashkin, Donald P.; Assassi, Shervin
Abstract : Objective: To assess the predictive significance of blood neutrophil count and the ratio between neutrophil and lymphocyte count (neutrophil‐to‐lymphocyte ratio [NLR]) for disease severity and mortality in systemic sclerosis (SSc). Methods: Neutrophil and lymphocyte counts were prospectively measured in the Genetics versus Environment in Scleroderma Outcome Study (GENISOS) and the Scleroderma Lung Study II (SLS II). Forced vital capacity percent predicted (FVC%) and modified Rodnan skin thickness score (MRSS) were used as surrogate measures for disease severity. Longitudinal analyses were performed using generalized linear mixed models. Cox proportional hazards models evaluated the predictive significance of these cell counts for mortality. Results: Of the 447 SSc patients in the GENISOS cohort at the time of analysis, 377 (84.3%) had available baseline blood neutrophil and lymphocyte counts. Higher baseline neutrophil count and NLR predicted lower serially obtained FVC% (b = −4.74, P = 0.009 and b = −2.68, P = 0.028, respectively) and higher serially obtained MRSS (b = 4.07, P < 0.001 and b = 2.32, P < 0.001, respectively). Longitudinal neutrophil and NLR measurements also significantly correlated with lower concurrently obtained FVC% measurements and higher concurrently obtained MRSS. Baseline neutrophil count and NLR predicted increased risk of long‐term mortality, even after adjustment for baseline demographic and clinical factors (hazard ratio [HR] 1.42, P = 0.02 and HR 1.48, P < 0.001, respectively). The predictive significance of higher baseline neutrophil count and NLR for declining FVC% and increased long‐term mortality was confirmed in the SLS II. Conclusion: Higher blood neutrophil count and NLR are predictive of more severe disease course and increased mortality, indicating that these easily obtainable laboratory studies might be a reflection of pathologic immune processes in SSc.